FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DI PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) TAHUN 2018-2022 - Mellya Embun Baining; Neneng Sudharyati; Al Akrom Alparidi (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The aim of this research is to determine the influence of Intellectual Capita, Good Corporate Governance, Accounting Conservatism on finance with company size as a moderating variable in companies registered on the Jakarta Islamic Index (JII) 2018-2022. Data used is quantitative source secondary data company financial reports for 2018-2022. Data analysis uses multiple linear regression and hypothesis testing. The research results obtained were that Intellectual capital and accounting conservatism had a significant effect on ROA in companies listed on (JII) 2018-2020, while good corporate governance had no significant effect on ROA in companies listed on (JII) 2018-2020. Intellectual capital has a significant effect on ROA with company size as a mediating variable in companies listed (JII) 2018-2020. Meanwhile, good corporate governance and accounting conservatism do not have a significant effect on ROA with company size as a mediating variable in companies listed (JII) for 2018-2020.